Caecal Herniation through the Foramen of Winslow: A Lesser Known Complication of the Lesser Sac - Charters, Pia; Lowe, Andrew; Keogan, Richard; Edwards, Tom (Journal of Gastrointestinal and Abdominal Radiology, 2019)
The foramen of Winslow is the omental communication between the greater and lesser sac. An internal hernia through the foramen of Winslow is extremely rare, accounting for <0.1% of abdominal hernias and 8% of internal hernias. The majority of lesser sac hernias contain small bowel only, less commonly cecum or omentum. Diagnostic delay is associated with high morbidity and mortality, and accurate radiological interpretation is invaluable to guide surgical intervention. As such, the recognition of foramen of Winslow herniation on computed tomography (CT) is paramount. We present a case of caecal herniation that was recognized early and reversed within 48 hours of presentation, without the need for bowel resection.
Keywords: cecum; foramen of Winslow; herniation; laparoscopic surgery; lesser sac